2019
DOI: 10.2298/apt1950304s
|View full text |Cite
|
Sign up to set email alerts
|

The effect of magnesium stearate and sodium starch glycolate on powder flowability

Abstract: The powder flow plays an important role in the manufacture of dosage form such as direct compression tablets. The objective of this research was to investigate the individual and interaction effects of magnesium stearate (MgSt) (Merck Ltd., Germany) as lubricant and sodium starch glycolate (SSG) (Primojel®) as superdesintegrator on powder flowability. Powder formulations were prepared by mixing different concentration of MgSt (0.25% and 5%) and SSG (0.5% and 4%) with microcrystalline cellulose (MCC) (Vivapur®1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…The compressibility test was intended to see the decrease in granule volume due to tapping accompanied by vibration. MPEM granules in the F3 formula had a good compressibility index with a value below 15 [ 44 ]. Based on the four test parameters, the formula with the best granule properties was a formula containing 5% w / w PVP K30 as a binder.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The compressibility test was intended to see the decrease in granule volume due to tapping accompanied by vibration. MPEM granules in the F3 formula had a good compressibility index with a value below 15 [ 44 ]. Based on the four test parameters, the formula with the best granule properties was a formula containing 5% w / w PVP K30 as a binder.…”
Section: Resultsmentioning
confidence: 99%
“…pressibility index with a value below 15 [44]. Based on the four test parameters, the formula with the best granule properties was a formula containing 5% w/w PVP K30 as a binder.…”
Section: Tablet Evaluationsmentioning
confidence: 99%
“…In order to investigate the flow properties of the filling, sieve analysis and rheological measurements were taken with the ground turmeric and with the final blend. The powder flow plays an important role in the manufacture of dosage form such as capsules and it is often a critical point of the process [36]. Proper powder flow allows uniform particle packing and a constant volume-tomass ratio which maintains capsule weight uniformity and consistent physicomechanical properties of capsule dosage forms [36].…”
Section: Discussionmentioning
confidence: 99%
“…The powder flow plays an important role in the manufacture of dosage form such as capsules and it is often a critical point of the process [36]. Proper powder flow allows uniform particle packing and a constant volume-tomass ratio which maintains capsule weight uniformity and consistent physicomechanical properties of capsule dosage forms [36]. Hardy et al has also reported that the appropriate flow properties of the final blend are necessary to the production of capsules with a consistent fill weight [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation